Hybrid feedback control - Sanfelice, Ricardo G. (Princeton University Press, 2021)
"Hybrid systems are those that-unlike classical systems-exhibit both discrete changes, or "jumps", and continuous changes, or "flow." The canonical example of a hybrid system is a bouncing ball: the ball's speed changes continuously between bounces, but there is a discrete jump in velocity each time the ball impacts the ground. Hybrid systems feature widely across disciplines, including in biology, computer science, and mechanical engineering; examples range from fireflies to self-driving cars. Although classical control theory provides powerful tools for analyzing systems that exhibit either flow or jumps, it is ill-equipped to handle hybrid systems, which feature both behaviors. In Hybrid Feedback Control, Ricardo Sanfelice presents a self-contained introduction to the control of hybrid systems, and develops new tools for their design and analysis. This monograph uses hybrid systems notation to present a new, unified control theory framework, thus filling an important gap in the control theory literature. In addition to presenting this theoretical framework, the book also includes a variety of examples and exercises, a Matlab toolbox, and a summary at the beginning of each chapter. The book was originally used in a series of lectures on the topic, and will find a modest amount of crossover course use. The book will also find use outside the field of control, particularly in dynamical systems theory, applied mathematics, and computer science"-- Provided by publisher
Keywords: Feedback control systems.; Hybrid systems.; Engineering mathematics.; Lyapunov functions.; elektronické knihy; electronic books